Mitochondrial DNA (Cytochrome c oxidase I) sequencing of Indian marine mussels - Divya, P R; Gopalakrishnan, A; John, Lijo; Thomas, P C; Lakra, W S (Indian Journal of Fisheries, 2016)
Two species of marine mussels, the green mussel Perna viridis (Linnaeus, 1758) and the brown mussel Perna indica (Kuriakoseand Nair, 1976) are found along the Indian coast. It had been suggested that P. indica, which occurs only along the Indiancoast, is a synonym of the globally distributed Perna perna. Along the south-west coast of India, where both P. viridis andP. indica co-exist, a third type referred to as parrot mussel, which has shell shape of brown mussel and color of green mussel(suspected to be their hybrid/morphotype) also occurs. The present investigation is a preliminary attempt for resolving thetaxonomic ambiguity among Indian marine mussel species using the mitochondrial cytochrome oxidase I (COI) gene.P. indica revealed 95% sequence similarity to P. perna. The sequence divergence between P. indica and parrot mussel wasnegligibly low (< 2%). Green mussel P. viridis showed 20.87% of sequence divergence with brown mussel P. indica as wellas with the parrot mussel.